Florida's Council of 100 and the Future of Water Supply Management in Florida - Roy R. Carriker (EDIS, 2003)
The purpose of this EDIS publication is to provide a synopsis of the task force report, including summaries of its findings and recommendations. This is EDIS document FE470, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.